Recognizing the Early Risk-Based Clinical Manifestations of Mucormycosis: Cornerstones for Improved Survival and Therapeutic Outcomes - Panagiotis Zagaliotis; Thomas J. Walsh (Journal of Fungi, 2025)
The early diagnosis and treatment of mucormycosis improves outcomes and saves lives [...]